STUDENTS’ ANXIETY IN SPEAKING ENGLISH AT MTs BUSTANUL ULUM TODDOLIMAE MAROS - Risma Fadillah; Warsidi Warsidi; Sitti Nurjannah (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
This research was conducted to find out the types and factors of students' anxiety in speaking English at MTs Bustanul Ulum Toddolimae Maros. The purpose of this study was to determine the types and factors of students' anxiety in speaking English at MTs Bustanul Ulum Toddolimae Maros. The researcher used descriptive qualitative approach. Data were collected through observation checklist and interview. The results showed that there were 3 types of anxiety in speaking English: communication anxiety, test anxiety, and fear of negative evaluation. Four anxiety factors experienced by students in their speaking anxiety are personal and interpersonal anxiety, learners' beliefs about language learning, language testing, and classroom procedures.